Outcomes of the COVID-19 pandemic in chronic lymphocytic leukemia : focus on the very early period and Omicron era - Hedberg, Pontus; Blixt, Lisa; Eketorp Sylvan, Sandra; Killander Möller, Isabela; Lindahl, Hannes; Kahn, Fredrik; Nilsdotter-Augustinsson, Åsa; Fredrikson, Mats; Nyström, Sofia; Bergman, Peter; Carlander, Christina; Aleman, Soo; et al. (Blood Advances, 2025)
Individuals with chronic lymphocytic leukemia (CLL) face an increased risk for severe COVID-19. This study from Sweden, a country that only had a few mandatory restrictions at the onset of the pandemic, used 10 nationwide registers to compare the risks for severe COVID-19 outcomes of polymerase chain reaction-verified severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections through February 2023 in individuals with and those without CLL. From a population of 8 275 839 (6653 CLL) individuals born between 1930 and 2003, 2 088 163 first infections (1289 CLL) were included. The 90-day all-cause mortality rate and adjusted relative risk (aRR; 95% confidence interval) for individuals with CLL vs the general population was 24.8% (1.95; 1.58-2.41) during wild-type, 17.2% (2.38; 1.58-3.57) during Alpha, 4.1% (0.71; 0.24-2.08) during Delta, and 12.6% (1.49; 1.24-1.78) during Omicron infections. Their mortality during Omicron was 0.6% (<65 years), 5.4% (65-74 years), and 19.7% (≥75 years). Small molecule inhibitors (1.56; 1.03-2.37) and corticosteroid usage (1.45; 1.04-2.02) was associated with increased mortality. Next, we analyzed the all-cause mortality in the capital (Stockholm), widely affected by SARS-CoV-2 at the onset of the pandemic. Mortality in individuals with CLL increased by 55% during the first 6 months of 2020 vs 2019, and the age- and sex-aRR by 30 June was 1.53 (1.09-2.15) for individuals with CLL (P = .02) and 1.29 (1.25-1.33) for the general population (P < .001). Collectively, a significantly increased risk for severe COVID-19 and death was observed among individuals with CLL in Sweden, particularly at the onset of the pandemic when few national protective measures were introduced and also after Omicron emerged, emphasizing the need for a more pro-active pandemic strategy for CLL.
© 2025 American Society of Hematology. Published by Elsevier Inc. Licensed under Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International (CC BY-NC-ND 4.0), permitting only noncommercial, nonderivative use with attribution. All other rights reserved.
Keywords: Humans; COVID-19/epidemiology; Leukemia, Lymphocytic, Chronic, B-Cell/complications; Female; Male; Aged; Sweden/epidemiology; Middle Aged; SARS-CoV-2/isolation & purification; Aged, 80 and over; Registries; Adult; Risk Factors; Pandemics